Intra‐Action in a Central Australian Community Development Project. Issue 2 (26th June 2022) - Anderson, Drew
ABSTRACT: Service providers commonly understand development projects in Indigenous Australia to play out at the intersection of a pre‐existing binary between Indigenous and non‐Indigenous groups. It follows that effective development practice is seen to depend on building partnerships across the 'intercultural' divide. Instead of taking this assumption as a baseline from which analysis proceeds, I draw on Karen Barad's theory of 'intra‐action' to show how an Indigenous/non‐Indigenous binary is continually produced in the context of a development NGO working in Central Australia. Based on fieldwork as a volunteer within this NGO, I demonstrate how the 'intra‐action' of community development process produces forms of difference and relatedness for non‐Indigenous NGO staff, and for the Aboriginal community. I argue that in spite of calls for deeper engagements, the community development apparatus continually performs separateness as the ethical framework on which the project proceeds. The paper contributes to debates around 'intercultural' anthropology and presents a non‐normative account of development practice in Australia.